Media Audiovisual Storytok sebagai Inovasi Pembelajaran Menulis Teks Narasi pada Siswa Kelas VIII SMP Negeri 6 Pamekasan - Adilla Zilfana Safira; Mochamad Arifin Alatas; Liana Rochmatul Wachidah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This research is motivated by the low interest and motivation of students in writing narrative texts caused by conventional learning methods and the lack of media that is interesting and relevant to students' digital world. This research aims to describe the use of TikTok-based StoryTok audiovisual media in learning to write narrative texts for class VIII students at SMP Negeri 6 Pamekasan. The method used is descriptive qualitative with data collection techniques in the form of observation and interviews. The research subjects were class VIII students, while the objects focused on the process and results of learning to write narrative texts through audiovisual media. The research results show that using StoryTok can increase students' interest and participation in writing, because this media is interactive, visual, and close to their daily lives. Apart from that, it is easier for students to understand narrative structure elements such as plot, characters and setting through creative audiovisual presentations. Technical obstacles such as internet access and application usage skills can be overcome through mentoring. The conclusion of this research is that StoryTok media is an effective digital learning innovation for improving narrative writing skills contextually, creatively and sustainably.Penelitian ini dilatarbelakangi rendahnya minat dan motivasi siswa dalam menulis teks narasi yang disebabkan oleh metode pembelajaran konvensional dan kurangnya media yang menarik serta relevan dengan dunia digital siswa. Penelitian ini bertujuan untuk mendeskripsikan penggunaan media audiovisual StoryTok berbasis TikTok dalam pembelajaran menulis teks narasi pada siswa kelas VIII SMP Negeri 6 Pamekasan. Metode yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data berupa observasi dan wawancara. Subjek penelitian adalah siswa kelas VIII SMP Negeri 6 Pamekasan, sedangkan objeknya difokuskan pada proses dan hasil pembelajaran menulis teks narasi melalui media audiovisual. Hasil penelitian menunjukkan bahwa penggunaan StoryTok mampu meningkatkan minat dan partisipasi siswa dalam menulis, karena media tersebut bersifat interaktif, visual, dan dekat dengan keseharian mereka. Selain itu, siswa lebih mudah memahami unsur struktur narasi seperti alur, tokoh, dan latar melalui penyajian audiovisual yang kreatif. Kendala teknis seperti akses internet dan keterampilan penggunaan aplikasi dapat diatasi melalui pendampingan. Simpulan dari penelitian ini adalah bahwa media StoryTok merupakan inovasi pembelajaran digital yang efektif untuk meningkatkan keterampilan menulis narasi secara kontekstual, kreatif, dan berkelanjutan.